Raum Assuan, Ägypten: Die Kulte muslimischer Heiliger - el-Shohoumi, Nadja (e-Forschungsberichte des DAI, 2023)
The veneration of muslim saints is a characteristic trait of Egyptian popular religion. The area of Aswan is dotted with sanctuaries of such saints which draw a large number of visitors, especially from the Nubian villages. These modern cults often stand in a clear relationship to historical sites; they cluster at the mausolea of the medieval necropolis of Aswan and they create a larger sacred landscape whose structure seems even to relate back to the pharaonic age. Since modern muslim orthodoxy threatens the very existence of these cults, an ethno-archaeological project was begun to document what can still be witnessed of such cult places and cultic practices.